Intra-Arterial Chemotherapy with Doxorubicin and Cisplatin Is Effective for Advanced Hepatocellular Cell Carcinoma. (22nd May 2014) - Ma, Ming-Chun; Chen, Yen-Yang; Li, Shau-Hsuan; Cheng, Yu-Fan; Wang, Chih-Chi; Chiu, Tai-Jan; Pei, Sung-Nan; Liu, Chien-Ting; Huang, Tai-Lin; Huang, Chen-Hua; Su, Yu-Li; Chen, Yen-Hao; et al.
Abstract : Advanced hepatocellular carcinoma (HCC) remains a fatal disease even in the era of targeted therapies. Intra-arterial chemotherapy (IACT) can provide therapeutic benefits for patients with locally advanced HCC who are not eligible for local therapies or are refractory to targeted therapies. The aim of this retrospective study was to analyze the effect of IACT with cisplatin and doxorubicin on advanced HCC. Methods . Patients with advanced HCC who were not eligible for local therapies or were refractory to sorafenib received doxorubicin (50 mg/m 2 ) and cisplatin (50 mg/m 2 ) infusions into the liver via the transhepatic artery. Between January 2005 and December 2011, a total of 50 patients with advanced HCC received this treatment regimen. The overall response rate (ORR) was 22% in all treated patients. In patients who received at least 2 cycles of IACT, the ORR was 36.7%, and the disease control rate was 70%. Survival rate differed significantly between patients who received only one cycle of IACT (group I) and those who received several cycles (group II). The median progression-free survival was 1.3 months and 5.8 months in groups I and II, respectively (P < 0.0001 ). The median overall survival was 8.3 months for all patients and was 3.1 months and 12.0 months in groups I and II, respectively (P < 0.0001 ). The most common toxicity was alopecia. Four patients developed grade 3 or 4 leukopenia. Worsening of liver function, nausea, and vomiting were uncommon side effects. This study demonstrated clinical efficacy and tolerable side effects of repeated IACT with doxorubicin and cisplatin in advanced HCC. Our regimen can be an alternative choice for patients with adequate liver function who do not want to receive continuous infusion of IACT.